LEARNING SYSTEM OF LINEAR EQUATIONS WITH APTITUDE TREATMENT INTERACTION MODEL FOR VOCATIONAL HIGH SCHOOL - Mulia, Tri Cahya; Aziz, Tian Abdul (KALAMATIKA Jurnal Pendidikan Matematika, 2023)
This project aims to employ the aptitude treatment interaction model in the teaching system of linear equations as an alternative learning approach for high school students pursuing vocational careers. Instructional design was utilized to develop the learning model. An essential aspect of applying the aptitude treatment interaction model to learning design is the analysis of student requirements. Learning outcomes and performance goals are thoughtfully considered and aligned with instructional objectives. The findings suggest that educators should utilize the aptitude treatment interaction model when teaching systems of linear equations. The effectiveness of the learning model depends on how well it is tailored to the student's abilities.